Gamificação como prática em equipes que adotam a autogestão - Rodrigues, André Pascoal (2023)
Gamification is able to stimulate the best in human beings by putting them in a situation with game-based activities. This is possible because games are part of human culture, as well as being part of everyday activities, such as work, for example. In fact, corporate gamification is considered a phenomenon that is attracting the attention of researchers and managers because of its promise of stimulating employee engagement and motivation to adopt behaviours that help achieve organizational objectives. The results of gamification in self-managing teams, however, are not yet known. Therefore, the aim of this experiment is to understand this practice in a software company where teams are self-managing. The format of corporate gamification is likely to produce a rhetoric of choice architecture or humanistic design, and identifying the materials, meanings and competencies of this practice is likely to be useful for understanding underlying and deeper aspects of gamification in self-managed teams. To this end, a qualitative approach was used, with Stake's (1995) single case study of the software company Flex as the research strategy. The components of the gamification practice mapped out are capable of giving rise to unique configurations of the practice in each team that adopts self-management, since they are constantly changing, since with each gamification challenge, new interactions between the elements are established by the practitioners. The main elements that emerged from the practice were the gamification platform as a material, the autonomy exercised by the teams as a skill and the healthy competition between the groups as a meaning. Gamification changed the social dynamics of the teams, since it promoted the development of new skills in the group members and increased the conviviality and connection between them. Therefore, gamification applied to self-managed teams is considered a means of regulating team autonomy, adjusted according to the software company's objectives. The study presented here hopes to contribute to software companies that want to give their staff more autonomy, because it points the way to a hybrid gamification that is ready to act both as a vehicle for monitoring performance and stimulating organizational playfulness and innovation.